Box-Cox transformation of monthly Malaysian gold price range - Gopal, Kathiresan; Abdul Rahim, Muhammad Firdaus; Adam, Mohd Bakri (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
Gold has a long history in trading over the past decades until its role in trading was replaced by the introduction of banknotes and coins. Gold is undeniably one of the prime commodities in investments and as well as a hedging tool. Thus, it is important to study the fluctuation in monthly gold price in Malaysia to extract useful information that could benefit investors and the government. In this paper, Box-Cox transformation was applied on the original data to deal with the presence of heteroscedasticity, non-normality and outliers. Monthly gold price data for the period of 2002 to 2011 were obtained to study its fluctuation using range as a measure of dispersion. It is found that the Malaysian gold price range is best described by the Normal distribution with parameters estimated using Maximum Likelihood Estimation.